Ethical considerations in wildlife medicine - Joyner, LoraKim (Wildlife Rehabilitation Bulletin, 2022)
<span style="color: #000000; font-family: -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen, Ubuntu, Cantarell, 'Fira Sans', 'Droid Sans', 'Helvetica Neue', sans-serif; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Component wildlife ethics includes two aspects: an understanding of ethical principles and skills in ethical deliberation. Ethical principles reviewed here include utilitarianism, deontological ethics, environmentalism or respect for nature, virtue ethics, relational ethics, care ethics and reverence for life ethics. Other processes and tools that take into account human sociology, behaviour and subconscious functioning in moral decision-making include conservation psychology, narrative ethics, socioscience, listening and communication skills, and needs-based ethics. We also take into account non-human functioning such as welfare science, conservation behaviour and cognitive ethology. Incorporating these tools and instituting ethical practices and programs within our wildlife and conservation management plans and organizations improve our ability to care for ourselves, other humans, wildlife and ecosystems.